System and method for managing objects stored in a cache - VIRK, NAVJOT; PARDIKAR, SHISHIR PURUSHOTTAM; STEERE, DAVID CAPPERS; AUST, BRIAN S; SAMJI, MOHAMMED; LIN, YUN (2008)
The present invention is directed at a system and method for managing and evicting objects stored in a cache. The invention provides a mechanism for determining which objects to evict based on a weight that is calculated for each object stored in the cache. The weight is determined by at least two factors, including file size, file type, primary user, last access time, and the like, and by the relative importance of each of the factors. The weight for each object may be determined autonomously and/or may be determined upon a trigger event. The factors and their relative importance may be obtained from a policy applicable to one or several computers.